2002
DOI: 10.1007/s004080000101
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Cytokeratin Fragment 19 (CYFRA 21-1) Serum Levels for Early Prediction of Recurrence of Adenocarcinoma and Squamous Cell Carcinoma in the Lung after Surgical Resection

Abstract: The purpose of this study was to evaluate the markers' clinical usefulness for early prediction of recurrence, by serial and simultaneous measurements of serum cytokeratin fragment 19 (CYFRA 21-1), before and after surgery on patients with non-small cell lung cancers (NSCLC). The 48 patients enrolled in this study had adenocarcinoma of the lung (adenoCa) (including 24 patients with recurrence and 24 patients without recurrence 1 year after surgery) and 48 patients with squamous cell carcinoma of the lung (SCC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
1
14
0
5
Order By: Relevance
“…In addition, independent prognostic value of lactate dehydrogenase, albumin, calcium, NSE, CEA, and DNA have been observed in various studies 7,14,18–20 . For monitoring systemic therapy and the early detection of recurrent disease in non‐small cell lung cancer patients, CYFRA 21–1 and circulating DNA were frequently reported to be useful 6,12–15,21–23 . However, little is known about the relevance of biochemical markers for the early prediction of therapy response prior to imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, independent prognostic value of lactate dehydrogenase, albumin, calcium, NSE, CEA, and DNA have been observed in various studies 7,14,18–20 . For monitoring systemic therapy and the early detection of recurrent disease in non‐small cell lung cancer patients, CYFRA 21–1 and circulating DNA were frequently reported to be useful 6,12–15,21–23 . However, little is known about the relevance of biochemical markers for the early prediction of therapy response prior to imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The good correlation of tumor markers with tumor recurrences, which was associated in some cases with a considerable lead time, was confirmed by further studies for CYFRA 21-1 in patients with adeno-and squamous cell cancer [7,36]. TPS was found to be superior to SCC concerning the detection of recurrent disease in the squamous cancer cell subtype [12], and superior to CEA in the adenocancer cell subtype [32].…”
Section: Detection Of Recurrent Diseasementioning
confidence: 50%
“…Serum CYFRA 21-1 level was not influenced by sex and smoking habits [38, 39], which was found to be an independent prognostic factor of survival and tumour relapse [40]. The meta-analysis about prognostic significance of CYFRA 21-1 has been studied in several articles, which have indicated that high level expression of CYFRA 21-1 implies a poor prognosis [32, 34, 4148]. In this study, we found that the 2-year overall survival in the high level group was significantly lower than that in the low level group group, which is consistant with studies previous.…”
Section: Discussionmentioning
confidence: 99%